The assessment of stat laboratory test ordering practice and impact of targeted individual feedback in an urban teaching hospital. Issue 1 (12th December 2013) - Sorita, Atsushi; Steinberg, Daniel I.; Leitman, Michael; Burger, Alfred; Husk, Gregg; Sivaprasad, Latha
<x xml:space="preserve">Abstract</x> BACKGROUND Overuse of inpatient stat laboratory orders ("stat" is an abbreviation of the Latin word "statim, " meaning immediately, without delay) is a major problem in the modern healthcare system. OBJECTIVE To understand patterns of stat laboratory ordering practices at our institution and to assess the effectiveness of individual feedback in reducing these orders. INTERVENTION Medicine and General Surgery residents were given a teaching session about appropriate stat ordering practice in January 2010. Individual feedback was given to providers who were the highest utilizers of stat laboratory orders by their direct supervisors from February through June of 2010. MEASUREMENTS The proportion of stat orders out of total laboratory orders per provider was the main outcome measure. All inpatient laboratory orders from September 2009 to June 2010 were analyzed. RESULTS The median proportion of stat orders out of total laboratory orders was 41.6% for nontrainee providers (N = 500), 38.7% for Medicine residents (N = 125), 80.2% for General Surgery residents (N = 32), and 24.2% for other trainee providers (N = 150). Among 27 providers who received feedback (7 nontrainees, 16 Medicine residents, and 4 General Surgery residents), the proportion of stat laboratory orders per provider decreased by 15.7% (95% confidence interval: 5.6%‐25.9%, P = 0.004) after feedback, whereas the decrease among providers who were high utilizers but did not receive feedback (N = 39) was not significant (4.5%; 95% confidence interval: 2.1%‐11.0%, P = 0.18). Monthly trends showed reduction in the proportion of stat orders among Medicine and General Surgery residents, but not among other trainee providers. CONCLUSIONS The frequency of stat ordering was highly variable among providers. Individual feedback to the highest utilizers of stat orders was effective in decreasing these orders. Journal of Hospital Medicine 2014;9:13–18. © 2013 Society of Hospital Medicine